(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The capacity to exercise mental, emotional, and behavioral control over oneself is referred to as self-regulation. It is a fundamental component of human functioning that is the basis for adaptive behavior and overall health and happiness. distinct parts of the prefrontal cortex (PFC) are responsible for distinct aspects of self-regulation; however, the PFC as a whole is essential to self-regulation and plays a crucial role in this process. This review focuses on the interaction between two essential processes involved in self-regulation: behavioral activation and cognitive control. Specifically, the paper examines the relationship between these two processes. In particular, we will analyze the published research on the brain mechanisms that are responsible for behavioral activation and cognitive control, as well as the ways in which these processes interact with one another to make self-regulation possible. In this section, we will also examine the significance of these findings for both the understanding of self-regulation deficits in clinical populations and the development of therapies aiming at increasing self-regulation.